Effects of germination and aeration treatment following segmented moisture conditioning on the γ-aminobutyric acid accumulation in germinated brown rice - Zhang, Qiang; Liu, Nian; Wang, Shuangshuang; Pan, Leiqing (International Journal of Agricultural and Biological Engineering, 2020)
Brown rice was treated by segmented moisture conditioning to reach the suitable water content and aerated with air for germination. The effects of germination and aeration treatment on the γ-aminobutyric acid (GABA) content in germinated brown rice were studied. The results showed that the germination rate, glutamic acid, glutamate decarboxylase activity and GABA content in germinated brown rice increased significantly and then decreased with the increase of germination and aeration treatment parameters. Correlation analysis also revealed that there was a significant positive correlation between GABA accumulation and glutamic acid content, glutamate decarboxylase activity. These results suggested that the aeration treatment during germination following segmented moisture conditioning could contribute to a high GABA content of germinated brown rice.Keywords: germinated brown rice, segmented moisture conditioning and aeration treatment, GABA, glutamic acid, glutamate decarboxylaseDOI: 10.25165/j.ijabe.20201305.5538Citation: Zhang Q, Liu N, Wang S S, Pan L Q. Effects of germination and aeration treatment following segmented moisture conditioning on the γ-aminobutyric acid accumulation in germinated brown rice. Int J Agric & Biol Eng, 2020; 13(5): 234–240.